Relasi Agama-Budaya dalam Tradisi Masyarakat Osing (Studi Ritual Mocoan Lontar Hadis Dagang) - Suhendra, Ahmad (Kopertais Wilayah I DKI Jakarta dan Banten, 2023)
The purpose of this article is to conduct an analysis regarding the Mocoan Lontar Hadith Trade tradition in Kemiren Village, Glagah, Banyuwangi, East Java. Many Osing people, who are the original Banyuwangi tribe, also live in the village. Apart from that, this article also aims to find out the construction of religious and cultural relations with the existence of trade hadith mocoan lontar in Osing society. Therefore, in this case the focus of this research was formulated on how does trading hadith affect the daily lives of the Osing people? How do the Osing people position trade hadith in relation to religion? To answer these questions, research data was collected by conducting an interview with one of the local traditional leaders. The data analysis techniques used are data reduction, data presentation and drawing conclusions. The results of the research show that there is the reading or mocoan of Lontar Trade Hadith as a form of preserving local traditions. The mocoan tradition is not only limited to culture, but there are religious aspects and philosophical values contained in the reading of the Mocoan Lontar Trade Hadith for the Osing people.